Transition mobilitaire et disparition des motos à Ho Chi Minh Ville - Huê-Tâm Jamme (EchoGéo)
A mobility transition is currently unfolding in Ho Chi Minh City, from motorbike to car and possibly transit-based regimes of urban mobility. This paper focuses on people’s lived experience of the socio-spatial transformations that ensue. Qualitative methods are used to investigate the position of individuals in regard to mobility transition policies, which are conceptualized as ‘worlding practices’. The core hypothesis is that individuals contribute at least in equal part as planners and decision-makers to implementing such practices. The results show that most interviewees, including motorbike-dependent individuals, are in favor of changing mobility practices and associated transformations of the urban space. Driven by an ideal of modernity and development to which they adhere, individuals themselves can be seen as “worlding;” indeed they play an active role in implementing the mobility transition, despite their being the subjects of resulting inequalities.